ANALYSIS OF THE IMPACTS OF CLIMATE POLICY AND ENERGY UNCERTAINTIES ON THE STOCK EXCHANGE: THE CASE OF TURKIYE AND AMERICA - Ilgin, Kubra Saka (Pressacademia, 2024)
Purpose- It can be stated that global uncertainty indices, which were developed to measure the effects of global uncertainties on markets and the economy, may have the potential to affect risk perception and investment strategies in the markets. Determining the direction and intensity of the impact of uncertainty and risks on stock markets has become very important for stock market investors under these conditions. This paper aims to comparatively examine how the Climate Policy Uncertainty Index (CPUI) and Energy Uncertainty Index (EUI), which are relatively newer than global uncertainty indices and have been the subject of fewer studies, affect stock prices in Borsa Istanbul 100 (BIST100) and Standard&Poors 500 (S&P500) stock exchanges, in a developing and developed country stock exchange. Methodology- The short and long-term relationships between global uncertainty indices and stock prices were investigated using the ARDL (Distributed Autoregressive Lag) Bounds Test. ARDL is an approach that has several advantages over classical cointegration methods. Findings- It was determined that CPUI and EUI significantly affected the S&P500 index both in the short and long term, positively and negatively, respectively. For BIST100, this effect was negative but statistically insignificant for both indices in the long-term. Conclusion- This paper has highlighted the impact of climate policy and energy uncertainty indices on stock prices, especially in developed countries. In this context, the study emphasizes that investors and policymakers in these countries, especially those considering investing in developed countries, should consider these uncertainty indices and closely monitor them to reduce risks in their risk assessments and optimize their investment strategies. The paper contributes to the existing literature by improving the understanding of how climate policy uncertainty affects financial markets in developed and developing economies. The findings suggest that investors and policymakers should consider different effects when assessing the financial impacts of climate policy and energy uncertainty. Future research could investigate how firms respond to such uncertainties and the financial impacts of corporate strategies at the sectoral level. Keywords: Uncertainty, climate policy uncertainty, energy uncertainty, stock exchange JEL Codes: C32, G01,G11 Purpose- It can be stated that global uncertainty indices, which were developed to measure the effects of global uncertainties on markets and the economy, may have the potential to affect risk perception and investment strategies in the markets. Determining the direction and intensity of the impact of uncertainty and risks on stock markets has become very important for stock market investors under these conditions. This paper aims to comparatively examine how the Climate Policy Uncertainty Index (CPUI) and Energy Uncertainty Index (EUI), which are relatively newer than global uncertainty indices and have been the subject of fewer studies, affect stock prices in Borsa Istanbul 100 (BIST100) and Standard&Poors 500 (S&P500) stock exchanges, in a developing and developed country stock exchange. Methodology- The short and long-term relationships between global uncertainty indices and stock prices were investigated using the ARDL (Distributed Autoregressive Lag) Bounds Test. ARDL is an approach that has several advantages over classical cointegration methods. Findings- It was determined that CPUI and EUI significantly affected the S&P500 index both in the short and long term, positively and negatively, respectively. For BIST100, this effect was negative but statistically insignificant for both indices in the long-term. Conclusion- This paper has highlighted the impact of climate policy and energy uncertainty indices on stock prices, especially in developed countries. In this context, the study emphasizes that investors and policymakers in these countries, especially those considering investing in developed countries, should consider these uncertainty indices and closely monitor them to reduce risks in their risk assessments and optimize their investment strategies. The paper contributes to the existing literature by improving the understanding of how climate policy uncertainty affects financial markets in developed and developing economies. The findings suggest that investors and policymakers should consider different effects when assessing the financial impacts of climate policy and energy uncertainty. Future research could investigate how firms respond to such uncertainties and the financial impacts of corporate strategies at the sectoral level. Keywords: Uncertainty, climate policy uncertainty, energy uncertainty, stock exchange JEL Codes: C32, G01,G11